THE INTERVENTION OF UNITED STATES IN LIBERALIZATION OF INDONESIAN OIL AND GAS INDUSTRY - Eka Toya Mustika (HI 16 UMY 146, 2016)
*146 Energy plays a bigger role in countries at an intermediate stage of economic development, because it often makes a large contribution to economic growth, especially in terms of GDP at this stage. The United States is a clear example of a country who always tries to fulfill their needs in energy for their own domestic needs even to maintain the power as super power state. Due to a big number of oil and gas resources in Indonesia, Indonesia is the one of target country of the U.S. to dredge their gold opportunity in exploring oil and gas sector. The condition of natural resources in Indonesia that is very potential has made the Multinational Corporations (MNCs) which is mostly come from America interested to invest in the country. With its power, the U.S. embraced the liberal principles influencing Indonesian oil and gas policy to apply to achieve their own interest. The involvement of U.S. in liberalized Indonesian oil and gas industry becomes an interesting issue to be analyzed. This undergraduate thesis will analyze how the U.S. intervention in terms of the application of liberal practice could occur in Indonesian oil and gas industry. Several theory and concepts, such as theory of neoliberalism, concept of international organization, and concept of structural power will be used to analyze the issue.